The land market with multifunctional land use: how to deal with infrastructure? - Caroline Rodenburg; Ron Vreeker (European Regional Science Association (ERSA), 2002)
There is at present much discussion in The Netherlands on so-called multifunctional land use. This concept addresses the challenge to combine several socio-economic functions in the same area, so as to save scarce space and to exploit economies of synergy. An important aspect in analysing multifunctional land use concerns the role of the land market. In general, the higher the degree of multifunctionality of land use, the more expensive it will become to realise. Therefore, one could question if a free land market would facilitate multifunctional land use in an optimal way, and if not, what the relevant forms of market failures are. Of all different land use functions, especially the infrastructure component is interesting to analyse, since it facilitates many other land use functions in a multifunctional setting. The provision of infrastructure, however, is generally different from the other land use functions, since the government instead of private investors usually provides it. The way the land market is organised could affect the composition of the different land use functions, including infrastructure. The present paper aims to offer a new contribution to the economics of land-use by addressing the differences between the (optimal) realisation of multifunctional land use in a free or a regulated land market. The importance of transport infrastructure for facilitating multifunctional land use will be explained, and an analysis will be made of possible consequences for the provision of transport infrastructure in a free land market compared to a regulated one.
Keywords: 330